A interdependência entre liberdade política e liberdade privada como uma exigência do estado democrático de direito: a síntese operada no pensamento de Kant - Rodrigo Antonio Calixto de Pina Gomes Mello (2014)
For the two meanings that is generally attributed to the idea of freedom in political terms, freedom as a possibility of the subject be the author of the conduct rules that are imposed to him, that in this study it is mentioned by political freedom, and freedom as a possibility of using a private space of life that is free of external interferences, that in this study is mentioned by private freedom, it was conceived various levels of importance along the history. If, in a first moment, the political freedom is vigorously born in Greek field, the private freedom receives, at this period, a precarious treatment in juridical terms. However, when it is noticed the juridical attribute of private freedom in Modernity, the political freedom is marginalized. The big meeting of both is done at the Democratic Rule of Law; political freedom and private freedom becomes interdependent: the area of private interdependency bounded by the own subject. Although it represents itself as an irremovable requirement only with the emergency of Democratic Rule of Law, the interdependency between these two dimensions of freedom can already be seen at Kants political philosophy. Combining the liberal traits presents in its thought with the reception in the political area of the idea of autonomy developed by him in his philosophy of moral, the legal legislation appears in Kant as a fruit of political freedom and aiming the promotion of private freedom.